Edukasi Digital dan Desain Logo Kelompok Sadar Wisata (Pokdarwis) Air Terjun Suka Alam Di Desa Sukabumi Kalimantan Timur - Aransyah, Muhammad Fikry; Atmaja, Muhammad Widya (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
In the community service program, this extraordinary condition in 2020 is a problem that will be raised in the form of increasing the empowerment of Suka Alam Waterfall tourism in Sukabumi Village and providing information to the community in Sukabumi Village. This community service aims to develop Suka Alam Waterfall tourism and increase community knowledge in Sukabumi Village. The community service program was carried out in Sukabumi Village, Kota Bangun District, Kutai Kartanegara Regency on July 8, 2020 until. August 18, 2020 using the face-to-face (interview) method represented by group members, face-to-face (online media). The steps to be taken to solve the problem are designing and making logo designs for the Suka Alam Waterfall Tourism Awareness Group (POKDARWIS), and making digital educational materials. It is hoped that this work program can help develop the Suka Alam Waterfall Tourism Awareness Group (POKDARWIS), as well as increase public knowledge information in Sukabumi Village.